TINJAUAN KONDISI FISIK, KIMIA DAN MIKROBIOLOGIS AIR KOLAM RENANG SUMARU ENDO DI DESA REMBOKEN KECAMATAN REMBOKEN KABUPATEN MINAHASA TAHUN 2012 - Elne Vieke Rambi (POLTEKKES KEMENKES MANADO, 2012)
Sumaru Endo pool is a pool located in the Village District Remboken Minahasa regency. The purpose of this study is to determine the pHysical, chemical, and microbiological water swimming pool in the village of Sumaru Endo Remboken Minahasa District. This research is a descriptive study, in which researchers want to describe their pHysical, chemical and microbiological condition of the pool water at the pool in the village Remboken Sumaru Endo. Research variables, namely the pHysical condition of water, chemical and microbiological water pool Sumaru Endo, which focused on turbidity, acidity (pH), residual chlorine, Total coliform bacteria and Figures. The population is the pool water Sumaru Endo and a sample of the water pool is determined by purposive sampling. There are two categories of research instrument research instrument is an instrument of research in the field and laboratory research instruments. The results on several parameters, namely the pHysical conditions (turbidity), chemical conditions (Chlor), microbiological conditions (Total coliform) and the rate of water germs swimming pool Sumaru Endo ineligible, chemical parameters (pH) of thewater pool Sumaru Endo suitably qualified in accordance with the requirements stated in the Permenkes RI No. 416/1990. Presumably the manager of the attraction Sumaru Endo can find information about the management and pool equipment in order to improve the quality of the pool water so that it meets the requirements for use as well as pay attention to the factors that affect water quality such as quality pool cleaning pools, pool water disinfectant dose right , protect water sources from a variety of pond pollution.